(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
A proverb is one of the genres of folk oral creativity with a compact form, but deep content, which was created on the basis of many centuries of life observations, socio-economic, political and cultural experiences of the people.According to their socio-ideological functions, proverbs mainly represent the worldview of the general public, and in some cases, of some social classes or groups. For this reason, the thematic scope of proverbs is very wide, and this scope cannot be limited to the sphere of partial life reality; there is no sphere of social existence that is not reflected in proverbs. Proverbs have a special educational significance due to the fact that they were created on the basis of many centuries of life experiences. Because every proverb is tested several times by people’s life experiences and living conditions over many years.